Tree seedling growth allocation of Castanopsis kawakamii is determined by seed-relative positions - Zhu, Jing; Jiang, Lan; Chen, Lyuyi; Jin, Xing; Xing, Cong; Liu, Jinfu; Yang, Yongchuan; He, Zhongsheng (Frontiers in Plant Science, 2023)
Plants allocate growth to different organs as a strategy to obtain limiting resources in different environments. Tree seeds that fall from a mother tree settle on, within, or below the forest floor and litter layer, and the relative positions can determine seedling biomass and nutrient allocation and ultimately affect survival to the sapling stage. However, how emerged seedling biomass and nutrients of each organ are affected by seeds in different positions is not yet completely understood in subtropical forests. Therefore, an experiment was conducted with seeds positioned above the litter layers of different thickness, on the forest floor, and beneath the litter layer, and the influence of seed position on biomass allocation and nutrient use efficiency of emerged seedlings of Castanopsis kawakamii was examined. The aim of the study was determining the optimal seed position to promote regeneration. Allocation strategies were well coordinated in emerged seedlings from different seed positions. Seedlings from seeds positioned above litter layers of different thickness (~40 and 80 g of litter) allocated growth to leaf tissue at the expense of root tissue (lower root mass fraction) and increased nitrogen (N) and phosphorus (P) accumulation and nutrient use efficiency. Seedlings from seeds positioned beneath a deep litter layer allocated most growth to roots (high root: shoot ratio, root mass fraction) to capture available resources at the expense of leaf growth. Seedlings from seeds positioned on the forest floor allocated most growth to roots to obtain limiting resources. Further, we also founded that these traits were clustered into three groups based on traits similarity, and the cumulative interpretation rate was 74.2%. Thus, seed relative positions significantly affected seedling growth by altering allocation of resources to different organs. The different strategies indicated that root N:P ratios (entropy weight vector was 0.078) and P nutrient use efficiency were essential factors affecting seedling growth in the subtropical forest. Of the seed positions, beneath a moderate litter layer (~40 g of litter) was the most suitable position for growth and survival of Castanopsis seedlings. In future studies, field and lab experiments will be combined to reveal the mechanisms underlying forest regeneration.